Soara Batak: The Batak People's Resistance Newspaper in the Colonial Period (1919-1932) - Ichwan Azhari (IHiS (Indonesian Historical Studies), 2022)
Newspapers have a very important position in the politics of the Indonesian independence movement. Soara Batak is the first independence movement newspaper published in Batakland. This newspaper became a medium of information and communication, for the political organization Hatopan Kristen Batak (HKB). The initial purpose of publishing this newspaper was to oppose Dutch colonialism and the threat of foreign plantation entrepreneurs who wanted to capitalize on Batakland for personal gain. This can be seen from the motto of this newspaper which is written: Oela tanom, Oelang digomak Oelando which means “Cultivate your land, so that the Dutch do not take it”. This newspaper's courage in criticizing the colonial rulers caused Soara Batak's movements to be closely monitored. Tuan M. H. Manullang and A. Soetan Soemoroeng, the dual HKB and Soara Batak received repressive measures from the colonial government for their bold and sharp writings. The presence of Soara Batak had an important role in the politics of the Batak people's movement, which succeeded in igniting the people's fighting spirit to want to oppose Dutch colonialism which was very oppressive.